(untitled) (JURNAL ADMINISTRASI PUBLIK, 2019)
The work environment is one of the factors that affect the performance of employees. An employee who works a work surroundings that support that an employee to work optimally will produce a good performance. However, if instead when an employee is on a work environment that does not support such as lack of facilities, unsafe workplaces, noisy and hot then it is certain performance results employees will be low. This research method using quantitative research i.e. research which analysed the data in statistics with the aim to find out whether the work environment affects employee performance. Data collection is done by way of spreading the now at 63 employees then the data processed using the SPSS version application 22. Work environment positive and significant effect on performance clerk Girian Subdistrict. Which means that the better work environment physical and non physical then the performance of employees. The work environment has a fairly strong correlation and significantly to the development of the performance of government employees Girian Subdistrict. Suggestions in this study is the importance of improving the atmosphere of the working environment is good and conducive in raising employee productivity and expected the Government Town of Bitung can maintain and improve the physical work environment and non-physical. Keywords: work environment, performance , Employees.